Algoritms for pH control - Niemi, A. J.; Jutila, P. k. (Rev. Téc. Fac. Ing. Univ. Zulia)
The acidity of solutions containing both weak and strong constituents simultaneously are discussed and algorithms for their control by feedback and feedforward are suggested.